Gamma irradiation effect on bioactive glasses synthesized with polyethylene-glycol template. Issue 1 (January 2016) - Veres, R.; Trandafir, D.L.; Magyari, K.; Simon, S.; Barbos, D.; Simon, V.
Abstract: Bioactive glasses of the CaO–SiO2 –P2 O5 system were synthesized through a sol–gel template method using polyethylene-glycol (PEG) with different molar weights. The samples were investigated by differential thermal analysis, X-ray diffraction and Fourier transform infrared spectroscopy. Electron paramagnetic resonance spectroscopy was employed to evidence possible structural defects and to reveal the response of the investigated glasses to gamma irradiation, and related effects on protein adsorption and samples bioactivity. PEG addition during samples synthesis induces structural changes within the glass matrix, which are dependent on PEG molar weights. At the same time, the use of PEG favors the occurrence of network defects. For the samples prepared with PEG of increased molar weight a lower apatite-forming ability was evidenced by the test carried out in simulated body fluid. It was also demonstrated that the network defects of samples affect the secondary structure of the protein adsorbed on the glass surfaces.